Single‐leg hop distance normalized to body height is associated with the return to sports after anterior cruciate ligament reconstruction - Shunsuke Ohji; Junya Aizawa; Kenji Hirohata; Takehiro Ohmi; Sho Mitomo; Tetsuya Jinno; Hideyuki Koga; Kazuyoshi Yagishita (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose To investigate the relationship between single‐leg hop distance (SLHD), normalized body height, and return‐to‐sports (RTS) status after anterior cruciate ligament reconstruction (ACLR) and to identify the cut‐off value for SLHD on the operated side. Methods Seventy‐three patients after primary ACLR (median 13.5 months) participated in this cross‐sectional study. Participants were divided into ‘‘Yes‐RTS’’ (YRTS) or ‘‘No‐RTS’’ (NRTS) groups based on a self‐reported questionnaire. SLHD was measured, and the limb symmetry index (LSI) and SLHD (%body height) were calculated. A minimum p‐value approach was used to calculate the SLHD cut‐off points (%body height) on the operated side that were strongly associated with the RTS status. Logistic regression analysis was used to analyse the association between RTS status and SLHD cut‐off point (%body height). Isokinetic strength and Tampa scale for kinesiophobia (TSK) were measured as covariates. Results Among 73 patients, 43 (59%) were assigned to the YRTS and 30 (41%) to the NRTS group. The 70% body height cut‐off point for SLHD on the operated side was most strongly associated with RTS status. In a logistic regression analysis including other covariates, SLHD (%body height) < 70% and TSK were negatively associated with RTS status. Except for two participants, the LSI of the SLHD exceeded 90% and there was no significant association between the LSI of the SLHD and RTS status. Conclusion Even after improvement in the LSI of the SLHD, planning rehabilitation with the goal of achieving SLHD over 70% body height may be important for supporting RTS after ACLR. Level of evidence Cross‐sectional study, Level IV